PENGGUNAAN OBSERVASI VISUAL DIGITAL PADA INTERAKSI GURU DAN ANAK DALAM KELAS PAUD - Anita Yus; Salim Salim (Universitas Negeri Medan, 2021)
The interactions in Indonesian early childhood classes are still traditionally done without using digital visuals. The impact is that the data obtained is difficult to be reexamined. Therefore, this paper focuses on how digital visual observation is applied in investigating the quality of teacher-child interactions, it is used to determine the context or individuals associated with interaction, the impact of teacher-child interactions on child development. Data was collected through observation on 6 teachers with the number of children was 15 children. The study found that visual data illustrates various features of teacher-child interaction. Digital video observation provides a holistic view on the process of interaction, dominance in teacher-child interactions, and the impact of interactions on children's development in documenting all features and processes of child development that cannot be captured through traditional observations. In particular, digital visual observation brings a new perspective and becomes an effective methodological tool for understanding teacher-child interactions.